IMPACT OF MARKETING BUDGET ALLOCATION ON FINANCIAL PERFORMANCE OF STARTUPS - Rathore, Aakanchha (ShodhKosh: Journal of Visual and Performing Arts, 2024)
The research examines the multi-faceted determinants of the financial performance and viability of startup firms, specifically addressing budgeting methods, online marketing strategies, and financial management. Based on 24 varied sources of scholarship, the study emphasizes the importance of lean and responsive budgeting principles in countering financial risks, particularly during economic uncertainties. It emphasizes growing dependence on digital marketing and data-driven analytics to maximize market involvement and enhance Return on Marketing Investment (ROMI). Literature further shows the pivotal function of strategic financial planning, literacy, and business intelligence systems to improve profitability, operating performance, and decision-making. Empirical findings show that the alignment of budgeting control, project management, and digital technologies has a direct influence on startup valuation, growth, and resilience in changing business environments. Moreover, cross-regional case studies—covering regions such as Southeast Asia, North America, and South America—offer contextual perspectives on financial challenges and innovations in startup ecosystems. This review serves as a foundational reference for entrepreneurs, financial planners, and policy-makers seeking to enhance startup success through informed resource allocation, strategic marketing, and performance metrics integration.